TEACHING METACOGNITIVE STRATEGIES TO IMPROVE STUDENTS’ LISTENING PROFICIENCY - Nian Masna Evawati; Zulkifli Zulkifli; Koryati Koryati (HOLISTICS, 2018)
The article had a focus to examine the effectiveness of metacognitive strategies in teaching listening using video media towards the listening proficiency of students in order to overcome the actual obstacles of listening in the class. The participants of the research were the fourth semester students of Chemical Engineering State Polytechnic of Sriwijaya. This study was quantitative research. The data collection techniques were taking scores of pretest and posttest done by the students and the data analysis technique was using t-test. The results presented that metacognitive strategies was effective in teaching listening to improve the listening proficiency of students and it indicated a sufficiently great difference of listening proficiency between experiment and control groups.